Selective laser melting of TiC reinforced 316L stainless steel matrix nanocomposites: Influence of starting TiC particle size and volume content. (15th August 2016) - AlMangour, Bandar; Grzesiak, Dariusz; Jenn-MingYang,
Abstract: Selective laser melting (SLM), an additive manufacturing technology, was utilized to process TiC/316L nanocomposite systems with different starting TiC particle sizes and volume contents. The influence of the starting TiC particle size and volume content on the constitutional phases, microstructural features, and mechanical properties of the SLM-processed nanocomposite parts was investigated. The densification behavior was controlled by both the starting TiC content and the particle size; the densification level was enhanced with the use of fine starting TiC particles owing to the improvement of the reinforcement–matrix wettability. In general, by increasing the volume content of the TiC, the hardness increased and the coefficient of friction (COF) and wear rate deceased owing to the combined effects of grain refinement and grain-boundary strengthening. However, in contrast to the starting coarse TiC particles, the SLM-part processed with the starting fine TiC particles shows better wear resistance, in particular at a 10–15% TiC content, owing to improved TiC dispersion throughout the matrix and increased density. Graphical abstract: Highlights: SLM was used to process TiC/316L nanocomposite systems. The starting TiC particle sizes and volume contents of the systems were different. The hardness increased but COF and wear rate deceased with increasing volume content. SLM-part processed with fine TiC particles had better wear resistance that that processed with coarse ones.